THE SOCIALIZATION OF ROLE EMPLOYMENT AGENCY IN COMMUNITY EMPOWERMENT MEDAN KRIO VILLAGE - Syati Manaharawan Siregar; Refli Renaldi; Sandhi Fialy Harahap (Sean Institute, 2023)
This paper existence of the Manpower Office provides training opportunities and improves the quality of labor for the community, expanding employment and placement of labor for the community is important to get a job. To overcome the abilities and skills (skills), the Manpower Office establishes a skills training program for the community to improve the ability of its human resources. Each empowerment program creates opportunities and encourages the development of skills and resources that make people more accountable for the tasks assigned to the community. Community empowerment aims at creating competitiveness that is determined by ability. As a supporter of activities, community institutions, and organizations provide opportunities for empowerment activities by obtaining and utilizing community rights. However, limited access, lack of knowledge, and conditions and conditions of the community are less supportive. Making people unable to compete with skills that can adjust to the needs of the job market or become independent business actors who benefit themselves and their environment.